The Local Inflammatory Responses to Infection of the Peritoneal Cavity in Humans: Their Regulation by Cytokines, Macrophages, and Other Leukocytes - Marien Willem Johan Adriaan Fieren (Hindawi Limited, 2012)
Studies on infection-induced inflammatory reactions in humans rely largely on findings in the blood compartment. Peritoneal leukocytes from patients treated with peritoneal dialysis offer a unique opportunity to study in humans the inflammatory responses taking place at the site of infection. Compared with peritoneal macrophages (pM𝜙) from uninfected patients, pM𝜙 from infected patients display ex vivo an upregulation and downregulation of proinflammatory and anti-inflammatory mediators, respectively. Pro-IL-1𝛽 processing and secretion rather than synthesis proves to be increased in pM𝜙 from infectious peritonitis suggesting up-regulation of caspase-1 in vivo. A crosstalk between pM𝜙, γ𝛿 T cells, and neutrophils has been found to be involved in augmented TNF𝛼 expression and production during infection. The recent finding in experimental studies that alternatively activated macrophages (M𝜙2) increase by proliferation rather than recruitment may have significant implications for the understanding and treatment of chronic inflammatory conditions such as encapsulating peritoneal sclerosis (EPS).